2017
DOI: 10.1080/00958972.2017.1282611
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II) bipyridine complexes: from synthesis and crystal structures to electrochemical and cytotoxicity investigation

Abstract: Complexes 1-4, [Ru(L)(bpy) 2 ]PF 6 , where bpy = 2,2′-bipyridine; L = 3-methylpyridine-2carboxylic acid (L1), 6-methylpyridine-2-carboxylic acid (L2), 5-bromopyridine-2-carboxylic acid (L3) and 6-bromopyridine-2-carboxylic acid (L4), were synthesized and characterized. The electrochemical character of the complexes was investigated by cyclic voltammetry revealing two reversible reduction waves in the negative range of potentials, most likely due to a reduction of the bipyridine moiety. Cytotoxicity studies by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Moreover, the azomethine oxime stretching band appeared in the spectra of newly synthesized complexes in the region from 1520 cm -1 to 1510 cm -1 pointing out the involvement of oxime nitrogens. The proposed binding mode is further supported by obvious intensity increasing of N -O band and minor negative shifts of 1-3 in comparison to the LH 2 [30]. Finally, in the area below 550 cm -1 , a novel set of three bands was observed for all three complexes, which were attributed to M -N, and M -O vibrations [39].…”
Section: Methodsmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, the azomethine oxime stretching band appeared in the spectra of newly synthesized complexes in the region from 1520 cm -1 to 1510 cm -1 pointing out the involvement of oxime nitrogens. The proposed binding mode is further supported by obvious intensity increasing of N -O band and minor negative shifts of 1-3 in comparison to the LH 2 [30]. Finally, in the area below 550 cm -1 , a novel set of three bands was observed for all three complexes, which were attributed to M -N, and M -O vibrations [39].…”
Section: Methodsmentioning
confidence: 56%
“…The interactions between metal complexes and DNA or HSA have been widely investigated using various spectroscopic [29,30], calorimetric [31], and electrochemical methods [32,33]. Electrochemical studies of these interactions are increasingly represented due to their low cost and the use of simpler and smaller devices in comparison to the spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%
“…5-Bromopicolinic acid, one of the derivatives of picolinic acid, attracted attention over a long period of time and acted as organic ligand to form metal-organic complexes [5][6][7][8][9][10][11]. One of the derivatives, the methyl-5-bromo-6-methylpicolinate, has been reported as single crystal structure elsewhere [12].…”
Section: Commentmentioning
confidence: 99%
“…As modern medicine imposes more stringent standards on the final clinical use, the concept of the entire metal drug is also undergoing major changes. Every research conducted needs to go through a rigorous process, including synthetic routes, structure and electrochemical characterization, in vitro and DNA targeting test, and protein inhibition test . Studies have shown that the ligand can be responsible for redox activity and anticancer activity. , It can also improve the solubility of the complex, reduce toxicity, and enhance specificity .…”
Section: Introductionmentioning
confidence: 99%